2022
DOI: 10.1055/s-0040-1713947
|View full text |Cite
|
Sign up to set email alerts
|

Additional Treatment after Collagenase Injections and Needle Fasciotomy for Dupuytren’s Disease: A Retrospective Cohort Study

Abstract: Introduction The aim of this study was to assess the rate of additional treatment after collagenase injection and needle fasciotomy, and what factors are associated with additional procedures for recurrence. Materials and Methods We retrospectively identified 201 adult patients who underwent collagenase injection and 19 patients who underwent needle fasciotomy for Dupuytren’s disease from 2012 to 2014. Outcomes included additional treatment of the same ray for either recurrence or persistence of contracture. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Thus, although Leafblad et al 22 demonstrated higher direct costs for fasciectomy than CCH, the cumulative costs when accounting for future reinterventions were higher for CCH than fasciectomy. Similarly, in a retrospective comparative study of collagenase injections and needle fasciotomy in 220 patients from 2012 to 2014, Arnold et al 24 found a greater need for additional treatment after CCH injections, which was primarily another CCH injection. In addition, in a model assessing cost-effectiveness using data from published studies and Medicare in a simulated cohort of 10,000 individuals with Dupuytren’s disease, Yoon et al 25 indicated that CCH injections were not preferred to fasciectomy or PNA for treating recurrent Dupuytren’s disease because of a higher incremental cost-effectiveness ratio, which is the cost in US dollars per quality-adjusted life year.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, although Leafblad et al 22 demonstrated higher direct costs for fasciectomy than CCH, the cumulative costs when accounting for future reinterventions were higher for CCH than fasciectomy. Similarly, in a retrospective comparative study of collagenase injections and needle fasciotomy in 220 patients from 2012 to 2014, Arnold et al 24 found a greater need for additional treatment after CCH injections, which was primarily another CCH injection. In addition, in a model assessing cost-effectiveness using data from published studies and Medicare in a simulated cohort of 10,000 individuals with Dupuytren’s disease, Yoon et al 25 indicated that CCH injections were not preferred to fasciectomy or PNA for treating recurrent Dupuytren’s disease because of a higher incremental cost-effectiveness ratio, which is the cost in US dollars per quality-adjusted life year.…”
Section: Discussionmentioning
confidence: 96%